Educar sem Deformar: Contribuições foucaultianas para a Filosofia da Educação - MANTOVANI, JOSÉ PASCOAL (2020)
The focus of this work is to relate Michel Foucault's Philosophy to the theme of Education. The hypothesis of this thesis is: in order to understand the constitution of the subjectivity of the subject, it is necessary to revisit the daily narratives of characters who experience the Education phenomenon. Such narratives assist in the perception of the deformative traits inherent in contemporary Education, as well as its consequences and intentions regarding the formative act. Narratives of students and teachers are presented in order to understand the impact of Education on this constitutive activity. The need to deconstruct subjectivities was assessed, so that another subjectivity of being becomes viable. The method that accompanied this thesis was post-structuralism and dialectical historical materialism. As bibliographic references, Foucault's texts were included, in addition to the comments of Castro, Veiga-Neto, Deleuze, Gutting, Bakthin among others. This research was divided into four themes, but, for didactic purposes, divided into five sections: the first chapter deals with the concept of Education; the second and third sections deal with Foucault's domains; the fourth section presents the narrative theory that will assist in hermeneutics in narratives; in the fifth and last section, we seek the dialectic between Foucault's philosophy, narrative theory and the narratives of the characters who corroborated this work. The investigation of this investigation circulates in the formative / deformative double present in the impact of education in the constitution of subjectivity. The thesis defended is that the deformative role of contemporary education is committed to elements related to the subject and not the formation and constitution of being. The expectation is that the outcome of this thesis will assist in the interpretation and articulation of Foucault's philosophy with the theme of education, in addition to contributing to future research in the field of Philosophy of Education and Educator Training.